Facility and maintenance management of Apartment Taman Sri Pinang Block A,B,C Butterworth Pulau Pinang / Nur Aina Yusrina Yusri - Yusri, Nur Aina Yusrina (Universiti Teknologi MARA UiTM,Perak, 2022)
Perbadanan Pengurusan Taman Sri Pinang (PPTSP) was my choice to under go my 12 week of Practical Training. The company was known as a Joint Management Bodies (JMB). During the 12 weeks period of practical training. I was supervised by Mr Hamizi Bin Abdul Hamid. I have been learned more about JMB and their procedure how to manage every account and maintain every facility provided for occupants in the apartment Taman Sri Pinang. Throughout my practical training. I was able to apply the skill and knowledge acquired from lecture to complete my work in practice. On the other hands, as a trainee, good attitude is a must to have in order to follow and complete the instruction given although it is a miscellaneous works. Lastly within 4 months practical training, I had gained in countable knowledge and experience and understand more on the roles of building surveying in facility and maintenance management of the building.